THE ROLE OF MOTIVATION AS AN INTERVENING VARIABLE IN THE RELATIONSHIP BETWEEN ORGANIZATIONAL CULTURE AND JOB SATISFACTION TOWARDS THE PERFORMANCE - Thaci, Hashim (JMRI Journal of Multidisciplinary Research and Innovation, 2025)
This study aims to determine the role of work motivation as a link between organizational culture and job satisfaction levels, and how it affects employee performance at PT. Cerestar Flour Mills. The method used in this study is quantitative with the application of Partial Least Square Structural Equation Modeling (PLS-SEM) analysis. A total of 76 respondents were selected using a purposive sampling technique. The results show that organizational culture has a significant role and has a positive influence on work morale (p = 0.000). Conversely, job satisfaction does not show a direct influence on employee performance (p = 0.886). Organizational culture also has a positive contribution to employee performance through an indirect increase in work motivation (p = 0.051)